Integration of Mapping Malnutrition Cases in Toddlers Based on Geographic Information System With Media Communication Information Education in Health - Wiryawan, I Gede; Perwiraningrum, Dhyani Ayu; Hudori, Huda Ahmad (International Journal of Healthcare and Information Technology, 2024)
In this study, the stunting case incidence mapping system has been further developed, and its integration with Communication, Information, and Education (KIE) media in the health sector. This study aims to increase knowledge about the world of health, especially related to stunting, through the integration of KIE media into data visualization of stunting cases. The results of developing this system integration include a fairly good level of acceptance from the community, as evidenced by the results of User Acceptance Testing (UAT) carried out on health workers and mothers with children under five. Functional testing of the system has also been completed with the conclusion that several features need to be improved. UAT testing obtained results worth 87%, and from functionality testing a success rate reached 90%, but all improvements have been completed. Future studies that can be carried out are to implement this integrated system more widely.